An Exploration of Determinants of Anemia in Pregnant Women at Buakayu Community Health Center Tana Toraja Regency - Erni Yetti R; Zadrak Tombeg; Anto J. Hadi; Sumardi Sudarman; Syamsopyan Ishak; Fitri Rahma Handayani (Journal of Public Health and Pharmacy)
Introduction: Anemia on pregnant women is a global health problem that has serious impacts on the mother and fetus. The objective of the study was to explore the determinants of anemia on pregnant women at Buakayu Community Health Center, Tana Toraja Regency.